Invisibility and Stigma: Experiences of Transgender and Gender Non-Conforming Individuals in South Korea - Kim, Eunha; Park, Hyun; Cho, Ye Ji; Jeon, Kyung Ah; An, Hyunju (Archives of Sexual Behavior, 2024)
In this qualitative study, we explored the challenges that transgender and gender non-confirming (TGNC) individuals face in South Korea. For this, we conducted in-depth interviews with 14 South Korean TGNC younger adults attending colleges or graduate schools and analyzed their data through consensus qualitative research. Analyses revealed that issues related to interpersonal relationships and medical transiting were major challenges perceived by participants. Four categories emerged in the domain of challenges in interpersonal relationships, including issues associated with family, romantic partner, coming out and outing, and transphobia and cisnormativity. In addition, two categories (i.e., medical difficulties and physical appearance-related distress) were included in the domain of challenges related to medical transition. Unique sources of stress for South Korean TGNC younger adults included high risk of being outed due to Korean resident registration numbers, dissatisfaction with bodily changes when transitioning, and misgendering caused by Korean’s different honorific titles depending on gender.
Keywords: Adult; Gender Identity; Humans; Republic of Korea; Social Stigma; Transgender Persons; Transsexualism; Gender dysphoria; Gender nonconformity; South Korea; Transgender